Peril and Promise: a Decade Later - Salmi, Jamil (International Journal of African Higher Education, 2016)
This paper examines the impact of the path-breaking 2000 report entitled “Higher Education in Developing Countries: Peril and Promise,” which called for scaling up investment in tertiary education and research as a key vehicle to equip developing countries with the knowledge and qualified manpower needed to fight poverty and accelerate economic growth. Written by a distinguished group of independent experts with financial support from several donor agencies, the report had a major influence on the policies of developing countries and the type of interventions that donor agencies fund to accompany the tertiary education development of these nations. The article also reviews major global changes in the context and content of higher education, the “quiet revolution” of quality assurance, the impact of disruptive factors such as the financial crisis, the technological revolution, the “excellence initiatives” in several countries, and gives recommendations on how to move forward. --- Cet article examine l’impact du rapport révolutionnaire publié en 2000 et intitulé « L’Enseignement supérieur dans les pays en voie de développement : Péril et promesse », qui préconisait un accroissement de l’investissement dans l’enseignement supérieur et la recherche comme vecteur essentiel pour munir les pays en voie de développement du savoir et de la main d’œuvre qualifiée nécessaires pour lutter contre la pauvreté et accélérer la croissance économique. Rédigé par un groupe distingué d’experts indépendants, avec le soutien financier de plusieurs organismes donateurs, le rapport eut une influence majeure sur les politiques des pays en voie de développement et le type d’interventions que les organismes donateurs financent pour accompagner le développement de l’enseignement supérieur de ces nations. Cet article passe en outre en revue les principaux changements mondiaux dans le contexte ainsi que dans le contenu de l’enseignement supérieur - la « révolution tranquille » de l’assurance qualité, l’impact de facteurs disruptifs tels que la crise financière, la révolution technologique, les « initiatives d’excellence » dans plusieurs pays - et donne des recommandations sur comment aller de l’avant.